STRATEGI PENINGKATAN SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH KOTA MALANG - Durratun Nashihah (PANGRIPTA, 2023)
The level of accountability for the performance of the Malang City Government in recent years has increased significantly, so a strategy is needed so that the value of accountability continues to increase. The purpose of this study is to provide an overview of strategies for improving accountability and performance management in the government in Malang City. The results of this study are strategies for increasing accountability and performance management in the Malang City Government, including the Regional Apparatus Organization conducting satisfaction surveys on the community in each of its services periodically, the need to strengthen SOPs (Standard Operating Procedures) in public services, increasing adjustments to standards and review programs by involving the community (citizen charter), increasing the level of intensity of coordination between regional devices in order to improve public service innovation, providing and managing community complaints facilities, encouraging service innovation in every regional apparatus, and socializing service evaluation policies on a regular basis.